2011
DOI: 10.21109/kesmas.v6i1.113
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor Determinan Permasalahan Pelayanan Kesehatan Ibu dan Anak

Abstract: Masalah kesehatan yang dihadapi Indonesia kini adalah status kesehatan masyarakat yang rendah, antara lain ditandai dengan angka kematian ibu dan bayi yang tinggi serta masih banyak indikator pelayanan kesehatan ibu dan anak (KIA) yang belum ideal. Penelitian ini bertujuan untuk mengetahuifaktor-faktor yang berhubungan dengan permasalahan pelayanan KIA. Desain penelitian yang digunakan pada penelitian ini adalah cross sectional, data faktor predisposisi dikumpulkan dari 550 orang responden yang tersebar di 4 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…This result aligned with one conducted by Zahtamal (2011), in Riau, stated that payment method related with health financing is free variable that has firm connection with infant health with p value = 0.001 and PR = 4.884. The result also support Fuadi in Zahtamal (2011), mentioning self health payment is economically suffering to mother and the family since health cost do expensive so they can't access sufficient health service.…”
Section: Research Results Onsupporting
confidence: 88%
See 1 more Smart Citation
“…This result aligned with one conducted by Zahtamal (2011), in Riau, stated that payment method related with health financing is free variable that has firm connection with infant health with p value = 0.001 and PR = 4.884. The result also support Fuadi in Zahtamal (2011), mentioning self health payment is economically suffering to mother and the family since health cost do expensive so they can't access sufficient health service.…”
Section: Research Results Onsupporting
confidence: 88%
“…This result different than Juliwanto in Zahtamal (2011), stated that there are still many believes in community that not suitable with health values become deciding factor in poor public health service, such as common habit in choose birth assistant. Parenden (2014) also showed that mother habit to choose birth process assistant strongly related with local tradition/culture.…”
Section: Research Results Onmentioning
confidence: 79%
“…Contoh dari fenomena ini adalah pada program Kesehatan Ibu dan Anak (KIA), dimana Angka Kematian Ibu (AKI) dan Angka Kematian Bayi (AKB) di beberapa wilayah masih cukup tinggi. Banyak penelitian yang menyatakan bahwa angka kejadian AKI dan AKB tinggi dikarenakan salah satu faktornya adalah akses yang sulit untuk mendapatkan pelayanan kesehatan (Laksono & Hidayati, 2008) (Zahtamal et al, 2011) (Laksono & Pranata, 2013) (Astuti & Laksono, 2014) (Suraya et al, 2016).…”
Section: Pendahuluanunclassified
“…Some were revealed through research such as the development of health promotion models for rural-based pregnant women in Banyumas (Gamelia et al, 2016). In addition, there is the effect of multilevel intervention in the promotion of occupational health against metabolic syndrome components among workers (Zahtamal & Chandra, 2011). Another study of empowerment for school cadres (small doctors) can improve handwashing behavior, through six stages of integrated School Health Efforts that are a combination of fit for school and school health efforts selected models (Solehati et al, 2017).…”
Section: Informationmentioning
confidence: 99%